Therapeutic options in glioblastoma multiforme: current trends and future perspectives - Gonçalves, Patrícia Nunes (2021)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.